Loss of Prestin Does Not Alter the Development of Auditory Cortical Dendritic Spines - L. J. Bogart; A. D. Levy; M. Gladstone; P. D. Allen; M. Zettel; J. R. Ison; A. E. Luebke; A. K. Majewska (Neural Plasticity, 2011)
Disturbance of sensory input during development can have disastrous effects on the development of sensory cortical areas. To examine how moderate perturbations of hearing can impact the development of primary auditory cortex, we examined markers of excitatory synapses in mice who lacked prestin, a protein responsible for somatic electromotility of cochlear outer hair cells. While auditory brain stem responses of these mice show an approximately 40 dB increase in threshold, we found that loss of prestin produced no changes in spine density or morphological characteristics on apical dendrites of cortical layer 5 pyramidal neurons. PSD-95 immunostaining also showed no changes in overall excitatory synapse density. Surprisingly, behavioral assessments of auditory function using the acoustic startle response showed only modest changes in prestin KO animals. These results suggest that moderate developmental hearing deficits produce minor changes in the excitatory connectivity of layer 5 neurons of primary auditory cortex and surprisingly mild auditory behavioral deficits in the startle response.